Efektivitas Alokasi Input Usahatani Padi dalam Program Upsus Pajale di Subak Gadungan Delod Desa, Desa Gadungan, Kabupaten Tabanan - I GEDE MADE ARTHA SUDEWA WIJAYA; I WAYAN WIDYANTARA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Effectiveness Allocation Inputs of Rice Farm in Upsus Pajale Programat Subak Gadungan Delod Desa, Gadungan Village, TabananRegencyUpsus Pajale is one of the Indonesian government programs to increase rice, corn,and soybeans production to achieve food self-sufficiency. Subak Gadungan DelodDesa is one of the beneficiaries Upsus Pajale program. This study aims todetermine the effect, effectiveness, and efficiency of production rice yield. Datacollection in this study was conducted from August to November 2015 with randomsampling method. The Cobb-Douglass equation was used to analyze the influencefactors of production to yield, effectiveness and efficiency allocation of productionfactors. The results showed all of production factors such as seed, urea fertilizer,NPK fertilizer, and pesticide affect on yield. The use all of production factors hasnot been effective yet as the value of effectiveness below 40 percent. However,Upsus Pajale program has been implemented very effective because the value ofproductivity more than 0.3 tons/hectare. All production factors has not beenefficienct accordingly their use can be increased. Suggestion can be given in thisresearch is the farmers should be more careful in the use of production factors, thegovernment should continue to support farmers. Researchers are expected to findout efficiency of allocation production factors in Upsus Pajale programs areas.